Effect of salinity on the metabolism and osmoregulation of selected ontogenetic stages of an Amazon population of Macrobrachium amazonicum shrimp (Decapoda, Palaemonidae) - Mazzarelli, C. C. M. [UNESP]; Santos, M. R. [UNESP]; Amorim, R. V. [UNESP]; Augusto, A. [UNESP] (FapUNIFESP (SciELO), 2015)
Probably as a function of their wide geographical distribution, the different population of Macrobrachium amazonicum shrimp may present distinct physiological, biochemical, reproductive, behavioral, and ecological patterns. These differences are so accentuated that the existence of allopatric speciation has been suggested, although initial studies indicate that the genetic variability of populations happen at an intraspecific level. Among the biological responses described for M. amazonicum populations, those regarding osmoregulation and metabolism play a key role for being related to the occupation of diverse habitats. To this effect, we investigated osmoregulation through the role of free amino acids in cell volume control and metabolism, through oxygen consumption in larvae (zoeae I, II, V and IX) and/or post-larvae of a M. amazonicum population from Amazon, kept in aquaculture fish hatcheries in the state of São Paulo. The results add information regarding the existence of distinct physiological responses among M. amazonicum populations and suggest that possible adjustments to metabolism and to the use of free amino acids as osmolytes of the regulation of the larvae and post-larvae cell volume depend on the appearance of structures responsible for hemolymph osmoregulation like, for example, the gills. In this respect, we verified that zoeae I do not alter their metabolism due to the exposition to fresh or brackish water, but they reduce intracellular concentration of free amino acids when exposed to fresh water, what may suggest the inexistence or inefficient performance of the structures responsible for volume regulation and hemolymph composition. On the other hand, in zoeae II and V exposed to fresh and brackish water, metabolism alterations were not followed by changes in free amino acids concentration. Thus it is possible, as the structures responsible for osmoregulation and ionic regulation become functional, that the role of free amino acids gets diminished and oxygen consumption elevated, probably due to greater energy expenditure with the active transportation of salts through epithelial membranes. Osmotic challenges also seem to alter throughout development, given that in zoeae II oxygen consumption is elevated on brackish water of 18, but in zoeae V it happens in fresh water. After M. amazonicum metamorphosis, free amino acids begin to play an important role as intracellular osmolytes, because we verified an increase of up to 40% in post-larvae exposed to brackish water of 18. The main free amino acids involved in cell volume regulation of ontogenetic stages evaluated were the non essential ones: glutamic acid, glycine, alanine, arginine, and proline. Interestingly, larvae from estuarine population studied here survived until the zoeae V stage in fresh water, but in some populations far from the sea, zoeae die right after eclosion in fresh water or they do not reach zoeae III stage. In addition, given that in favorable conditions caridean shrimp larvae shorten their development, we may infer that the cultivation environment, in which larvae developed in the present work, was appropriate, because almost all zoeae VIII kept on brackish water underwent metamorphosis directly to post-larvae and did not go through zoeae IX stage.

Provavelmente como função da sua ampla distribuição geográfica, as diferentes populações do camarão Macrobrachium amazonicum podem apresentar distintos padrões fisiológicos, bioquímicos, reprodutivos, comportamentais e ecológicos. Essas diferenças são tão acentuadas que tem sido sugerido a existência de especiação alopátrica embora estudos iniciais indiquem que a variabilidade genética das populações ocorre ao nível intraespecífico. Dentre as respostas biológicas descritas para as populações de M. amazonicum, aquelas relacionadas à osmorregulação e metabolismo têm papel central por estarem relacionadas à ocupação dos diversos habitats. Nesse sentido, investigou-se a osmorregulação, por meio do papel dos aminoácidos livres no controle do volume celular e o metabolismo, por meio do consumo de oxigênio, em larvas (zoeas I, II, V e IX) e/ou pós-larvas de uma população de M. amazonicum oriunda da Amazônia e mantida em viveiros de aquicultura no estado de São Paulo. Os resultados adicionam informações a respeito da existência de respostas fisiológicas distintas entre as populações de M. amazonicum e sugerem que possíveis ajustes no metabolismo e no uso de aminoácidos livres como osmólitos da regulação do volume celular das larvas e pós-larvas dependem do surgimento de estruturas responsáveis pela osmorregulação da hemolinfa como, por exemplo, as brânquias. Nesse sentido, verificou-se que as zoeas I não alteram seu metabolismo em função da exposição à água doce ou salobra, mas reduzem a concentração intracelular de aminoácidos livres quando expostas à água doce, o que pode sugerir a inexistência ou um desempenho ineficiente das estruturas responsáveis pela regulação do volume e composição da hemolinfa. Por outro lado, nas zoeas II e V expostas à água doce ou salobra alterações no metabolismo não foram acompanhadas por mudanças na concentração dos aminoácidos livres. Assim é possível que à medida que estruturas responsáveis pela osmo e ionorregulação tornam-se funcionais, o papel dos aminoácidos livres se torne reduzido e o consumo de oxigênio elevado, provavelmente em função do maior gasto energético com o transporte ativo de sais através das membranas epiteliais. Os desafios osmóticos também parecem se alterar ao longo do desenvolvimento visto que em zoeas II o consumo de oxigênio é elevado em água salobra de 18 mas em zoeas V essa resposta ocorre em água doce. Após a metamorfose de M. amazonicum, os aminoácidos livres passam a ter papel importante como osmólitos intracelulares, pois se verificou um aumento de até 40% nas pós-larvas expostas à água salobra de 18. Os principais aminoácidos livres envolvidos na regulação do volume celular dos estágios ontogenéticos avaliados foram os não essenciais ácido glutâmico, glicina, alanina, arginina e prolina. Interessantemente, as larvas da população estuarina aqui estudada sobrevivem até o estágio de zoea V em água doce mas em algumas populações distantes do mar as zoeas morrem logo após a eclosão em água doce ou não chegam ao estágio de zoea III. Adicionalmente, visto que em condições favoráveis as larvas de camarões carídeos abreviam o seu desenvolvimento pode ser inferido que o meio de cultivo em que as larvas se desenvolveram no presente trabalho foi adequado, pois quase todas as zoeas VIII mantidas em água salobra sofreram diretamente a metamorfose para pós-larvas e não passaram pelo estágio de zoeas IX.
Keywords: Macrobrachium; Osmorregulation; Crustacea; Metabolism; Physiology; Macrobrachium; Osmorregulação; Crustacea; Metabolismo; Fisiologia